TOWARD THE STUDY OF ETIOLOGIC AND EPIDEMIOLOGIC CHARACTERISTICS OF A NEW CORONAVIRUS INFECTION (COVID-19) IN THE WORLD - Ulmasova S.I; Kasimov I.A (Scholar Express Journals, 2024)
To date, more than two hundred viruses causing respiratory infections in humans have been discovered and studied. At the same time, the emergence of pathogens is, firstly, a natural process that reflects the natural course of biological evolution, and, secondly, the result of active development of molecular diagnostic methods. Most newly discovered pathogens are represented by viruses [1, 2, 3, 16]. The etiologic spectrum of acute respiratory viral infections has been expanded due to the "newest" viruses discovered at the beginning of the 21st century. Such pathogens include the new coronavirus [3,4,6].
Keywords: coronavirus infection; pandemic; etiologic structure of the virus